2010
DOI: 10.1186/1471-2407-10-631
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EGFR/HER2 pathways enhances the antiproliferative effect of gemcitabine in biliary tract and gallbladder carcinomas

Abstract: BackgroundAdvanced biliary tract carcinomas (BTCs) have poor prognosis and limited therapeutic options. Therefore, it is crucial to combine standard therapies with molecular targeting. In this study EGFR, HER2, and their molecular transducers were analysed in terms of mutations, amplifications and over-expression in a BTC case series. Furthermore, we tested the efficacy of drugs targeting these molecules, as single agents or in combination with gemcitabine, the standard therapeutic agent against BTC.MethodsImm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(119 citation statements)
references
References 46 publications
5
112
2
Order By: Relevance
“…Human recombinant EGF (Peprotec EC, Rocky Hill, NJ, USA), human recombinant HGF (R&D Systems, Minneapolis, MN, USA), and Wnt inhibitor (IWP3; Miltenyi Biotec, Bergisch Gladbach, Germany) were purchased. The effect of various concentrations of EGF (1,5,10,25,50, 100 ng/mL) and HGF (1,10,30,60, 120 ng/mL) on morphology was examined in GBC cells. At 10 ng/mL and higher concentrations of EGF, and at 30 ng/mL and higher concentrations of HGF, there were clear effects on cell morphology (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human recombinant EGF (Peprotec EC, Rocky Hill, NJ, USA), human recombinant HGF (R&D Systems, Minneapolis, MN, USA), and Wnt inhibitor (IWP3; Miltenyi Biotec, Bergisch Gladbach, Germany) were purchased. The effect of various concentrations of EGF (1,5,10,25,50, 100 ng/mL) and HGF (1,10,30,60, 120 ng/mL) on morphology was examined in GBC cells. At 10 ng/mL and higher concentrations of EGF, and at 30 ng/mL and higher concentrations of HGF, there were clear effects on cell morphology (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…(7) Amplification and point mutations of the EGFR gene have been reported to be 1% and 15 -26.5%, respectively, in GBC. (8)(9)(10) The HGF receptor c-Met is involved in the early carcinogenesis of BTC. (11) c-Met is expressed in 74% of invasive GBC and is associated with invasive depth.…”
mentioning
confidence: 99%
“…Its amplification or overexpression has been shown to play an important role in the development and progression of several solid tumor malignancies, and is an effective therapeutic target in breast and gastric cancer (41)(42)(43). Studies evaluating HER-2 overexpression in BC have identified HER-2 mutations in gallbladder (about 10%) and EHCCs (up to 25%), and have been associated with a more aggressive phenotype (27,44). While small case series demonstrated anti-tumor activity with anti HER-2 directed therapy in patients whose tumors expressed HER-2 overexpression or amplification, these findings did not translate in BC patients Novel genomic alterations identified in IHCC…”
Section: Her-2/neu Genementioning
confidence: 99%
“…ErbB receptors and the binding to its ligands are integral to biliary carcinogenesis. Anti EGFR and HER-2 therapies have demonstrated interesting anti-tumor activity in preclinical studies (27), resulting in their investigation in clinical trials. …”
Section: Erbb Family Signaling Pathway In Bcmentioning
confidence: 99%
“…In in vivo studies, the authors found that oral administration of sorafenib significantly inhibited tumor growth of heterotopic xenografts [58]. Other in vitro study has shown the existence of synergy in the combined use of sorafenib with doxorubicin and gemcitabine in CC treatment [62].…”
Section: Diagnosis and Treatmentmentioning
confidence: 94%